CHARACTERIZATION OF THE CORECEPTOR DOMAIN OF T CELL ANTIGEN COUPLERS IN CANCER IMMUNOTHERAPY - MWAWASI, KEN (My University, 2020)
Activating the immune system in the therapeutic treatment of cancer is rapidly growing and has demonstrated tremendous success. One such method is engineering T cells with chimeric antigen receptors (CARs) to specifically direct them in targeting tumours, however this has been associated with several toxicities that may be linked to the synthetic nature of the CAR. To address this, our laboratory created the T Cell Antigen Coupler (TAC), an alternative receptor that redirects T cells in a more natural TCR-dependent fashion. The TAC consists of three components: the antigen-binding domain that recognizes a tumour antigen, a TCR-recruitment domain that co-opts the native CD3-TCR complex and a CD4 co-receptor domain. The TAC displays unique biology, specifically in the increased antitumor infiltration and clearance of solid malignancies without any of the observed host toxicities seen with CARs. The functionality of the TAC was shown to be dependent on both the antigen binding and TCR-recruitment domains, however the co-receptor domain remains relatively uninvestigated despite evidence in the literature indicating its importance in endogenous T cell activation. This thesis seeks to better understand the biology of the TAC receptor by investigating the contributions of co-receptor domain. In Chapter 3, we replaced the CD4 co-receptor domain with CD8 variants and showed that the TAC retains functionality. In Chapter 4, we removed the cytosolic domain of the TAC in its entirety (creating a “tailless TAC”) and observed increased in vivo efficacy. In Chapter 5, we evaluated the tailless TAC in different cancer models and consistently observed increased in vivo efficacy compared to the full length TAC. These results demonstrate an increase in the in vivo functionality of the TAC receptor when the cytoplasmic tail is removed, giving us further insights into the mechanisms behind the unique biology of the TAC receptor.
Keywords: immunotherapy; cancer; T cell; TAC; coreceptor; immunology